Review Paper on Big Data and Its Significance (International Journal of Innovative Research in Computer Science & Technology, 2021)
Academic and businesses alike are  growing increasingly fascinated in business intelligence  as the requirement for analyzing patterns in massive  databases grows. As sensors nodes and computer crimes  platforms expand, the amount of data collected has  increased dramatically. Data from cameras, online  networks, and economic information are intrinsically  worthless due to distortion, unfinished information, and  unpredictability. This article serves two purposes.  Various big data tools are also addressed in the article,  along with their distinguishing features. These areas have  many research paths, but the purpose of this article is to  allow exploration of these topics as well as the  development and execution of optimal Big Data methods.  Researchers interested in studying and participating in  this rapidly expanding field will be able to learn about  present trends as well as potential future directions. This  article looks at big data, its challenges, and where it is headed in the future, as well as the Big Data Analytics  methods used by various companies to help them make  good investment decisions. This research, on the other  hand, is limited to big data concepts and the issues they  can solve. The goal of this paper is to look at the  problems and roadblocks that are becoming more  prevalent in this new industry.
Keywords: Analytics; Big Data; Machine Learning; Storage; Technologies